Virtual mobility and the EQF : using e-learning to widen access and enhance quality higher education across Europe - Teixeira, António (2011)
One of the major goals of the European Higher Education Area (EHEA) is to facilitate the mobility of citizens, assuring the transparency and competitiveness of qualifications across Europe. The formal adoption of the European Qualifications Framework (EQF) represented an important step in that direction, contributing to achieve mobility in higher and continuing education. However, the full engagement of European institutions and students in this process, can only be possible through the wide-spread use of e-learning. Yet, institutions and students struggle with the lack of a clear theoretical framework and a set of tools that enable virtual mobility of students, guaranteeing EQF implementation through e-learning. One of the critical issues being the transferability of credits, since there isn’t a common understanding or any European standards on how to calculate credit units in e-learning courses. In this paper, we present a possible solution for transferability of credits in e-learning courses across the EHEA in accordance with the EQF.